On the oxidation mechanism of refractory high entropy alloys. (October 2019) - Müller, Franz; Gorr, Bronislava; Christ, Hans-Jürgen; Müller, Julian; Butz, Benjamin; Chen, Hans; Kauffmann, Alexander; Heilmaier, Martin
Highlights: The formation of CrTaO4 after a short incubation period decreased the oxidation kinetics of Ta-containing alloys. Activation energies for scale growth comparable to those of Cr2 O3 and CrTaO4 forming Ni-based superalloys were found. The oxygen inward diffusion was found to be rate determining in CrTaO4 forming alloys. In Nb-containing alloys, the formation of Nb2 O5 caused a porous oxide scale as well as severe oxide spallation. Ti had a positive effect on the high-temperature oxidation behaviour because it supports the formation of protective CrTaO4 . Abstract: The high-temperature oxidation mechanism of a series of refractory high entropy alloys: TaMoCrTiAl, NbMoCrTiAl, NbMoCrAl and TaMoCrAl at 1000 °C in air was studied. A complex protective oxide layer consisting of Al2 O3, Cr2 O3 and CrTaO4 oxides was observed for the quinary Ta-containing alloy. The formation of CrTaO4 in this alloy after a short incubation period decreased the oxidation kinetics from a parabolic to a quartic rate law. Ti was found to support the formation of CrTaO4 . In the Nb-containing alloys, the formation of different Nb2 O5 polytypes near the metal/oxide interface caused a highly porous oxide scale and severe oxide spallation.